Effective Content Strategy to Boost Halal Product Brands - Sayful Arif; Sholahuddin Sholahuddin; Tatha Amelia Fretika; Devi Triana; Lailatul Fitria; Hawa Gazani (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
The development of digital technology has brought significant changes to marketing strategies, including for halal products, which are increasingly in demand by global consumers. Halal products are not only required to meet Sharia standards but also to build trust and brand awareness in a competitive market. This study aims to examine effective digital content strategies for enhancing halal product brands in the digital era. The method used was a qualitative approach through case studies of halal business actors using interviews, focus group discussions (FGDs), observation, and documentation. The results show that informative, educational, and consistent content strategies optimized with SEO and social media can increase halal product visibility, strengthen brand image, and foster consumer loyalty. Collaboration with influencers and creative use of digital platforms have also proven effective in expanding marketing reach. Thus, a targeted content strategy serves not only as a promotional tool but also as an educational and communication tool that supports the sustainability of the halal product business.